2014
DOI: 10.1007/s11804-014-1273-7
|View full text |Cite
|
Sign up to set email alerts
|

The current situation of the study on twisted tape inserts in pipe exchangers

Abstract: Heat transfer enhancement is used in many applications including heat exchangers, air conditioning, and refrigeration systems; hence many researchers have conducted experimental and numerical researches on heat transfer enhancement and have developed various techniques and methods. As a passive heat transfer technique, twisted tapes are widely used in various industries for their cost savings, lower maintenance requirements and the fact that they are easily set up. This paper introduces the principle of heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A comprehensive literature review on twisted tape inserts indicated that previous studies concentrated mainly on the laminar flow regime for Reynolds numbers between 13 and 3 000 [2,5,15,[37][38][39][40][41][42][43][44][45] or the turbulent flow regime for Reynolds numbers greater than 3 000 [4,29,33,[46][47][48][49][50][51] and not specifically on the transitional flow regime [52][53][54][55]. Up to now, only Wongcharee and Eiamsa-ard [15] (in the laminar flow regime) and Eiamsa-ard and Promvonge [4] (in the turbulent flow regime), considered alternating clockwise and counter clockwise twisted tape (CCCTT)…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature review on twisted tape inserts indicated that previous studies concentrated mainly on the laminar flow regime for Reynolds numbers between 13 and 3 000 [2,5,15,[37][38][39][40][41][42][43][44][45] or the turbulent flow regime for Reynolds numbers greater than 3 000 [4,29,33,[46][47][48][49][50][51] and not specifically on the transitional flow regime [52][53][54][55]. Up to now, only Wongcharee and Eiamsa-ard [15] (in the laminar flow regime) and Eiamsa-ard and Promvonge [4] (in the turbulent flow regime), considered alternating clockwise and counter clockwise twisted tape (CCCTT)…”
Section: Introductionmentioning
confidence: 99%
“…Heat exchange tube processes are indispensable in numerous sectors: heating & cooling, refrigeration, automobile radiators, winery, food processing, pharmaceuticals, Petrochemicals, chemicals, oil, steel, agriculture, and manufacturing [1]. Proficient and optimal thermal energy transfer is paramount for the production, preservation, and conveyance of diverse goods.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature review on twisted tape inserts indicated that previous studies concentrated mainly on the laminar flow regime for Reynolds numbers between 13 and 3 000 [2,5,15,[37][38][39][40][41][42][43][44][45] or the turbulent flow regime for Reynolds numbers greater than 3 000 [4,29,33,[46][47][48][49][50][51] and not specifically on the transitional flow regime [52][53][54][55]. Up to now, only Wongcharee and Eiamsa-ard [15] (in the laminar flow regime) and Eiamsa-ard and Promvonge [4] (in the turbulent flow regime), considered alternating clockwise and counter clockwise twisted tape (CCCTT) inserts.…”
Section: Introductionmentioning
confidence: 99%